Development of a Digital Game-Based Mathematics Learning Application for Elementary School Students - Siti Arofah; Saryanto Saryanto; Rahmat Mulyono (CV Edujavare Publishing, 2026)
This study aimed to develop and evaluate the effectiveness of a digital game-based mathematics learning application for elementary school students at SD Negeri 2 Rojoimo. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, expert validation sheets, questionnaires, and learning achievement tests. The developed application integrated mathematics learning materials with interactive game elements, including levels, rewards, challenges, animations, and immediate feedback to enhance student engagement and learning experiences. The validation results indicated that the application met the criteria for content accuracy, media quality, and instructional appropriateness, making it suitable for classroom implementation. Furthermore, the implementation findings revealed that the application significantly improved students’ learning motivation, participation, self-directed learning, positive attitudes toward mathematics, and mathematics achievement. Students demonstrated greater enthusiasm and engagement during learning activities, while the interactive features supported better understanding of mathematical concepts. These findings suggest that digital game-based learning applications can serve as effective instructional tools for improving both cognitive and affective learning outcomes in elementary mathematics education and provide innovative solutions for technology-enhanced learning in the digital era.